THE INFLUENCE OF SOME PLANT EXTRACTS ON THE FEEDING ACTIVITY OF SMALL RICE GRASSHOPPER, OXYA HYLA HYLA - MARNGAR, DAININGSTAR; KIHARBULI, B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2001)
<span style="color: #000000; font-family: Roboto, sans-serif; font-size: 13px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; background-color: #ffffff; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The selected plant extracts have been tested against the feeding activity of the small rice grasshopper. Oxya hyla hyla. Among all the plant extract tested, Ageratum conyzoides methanolic extracts at 50, 100 and 200 mg/ml concentrations were observed to be the most effective, although other plant extracts also show inhibition and cessation offeeding.